Persistence Programming. - COBBS, ARCHIE L. (Communications of the ACM, 2022)
This article presents an overview on persistence programming, defining it and exploring the accuracy of its usage. Topics include Java Persistence API, application programming interface, compared to developing persistence programming based on the programmer’s needs, and a discussion on what defines the underlying database.